2016
DOI: 10.2147/ijwh.s107586
|View full text |Cite
|
Sign up to set email alerts
|

Continuation rates, bleeding profile acceptability, and satisfaction of women using an oral contraceptive pill containing estradiol valerate and dienogest versus a progestogen-only pill after switching from an ethinylestradiol-containing pill in a real-life setting: results of the CONTENT study

Abstract: BackgroundOral contraceptives are still associated with high discontinuation rates, despite their efficacy. There is a wide choice of oral contraceptives available, and the aim of this study was to assess continuation rates, bleeding profile acceptability, and the satisfaction of women in the first year of using a contraceptive pill containing estradiol valerate and dienogest (E2V/DNG) versus a progestogen-only pill (POP) in a real-life setting after discontinuing an ethinylestradiol-containing pill.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In a European Phase III trial, with 20 cycles of observation, only 2.5% of women discontinued treatment prematurely due to bleeding irregularities 13. Our data are higher than the above, but quite similar to those of a large clinical study performed in a real-life setting (27.7%) 14. The discontinuation rate for irregular bleedings that we observed with E2-COCs was higher than that (5.3%) observed in a previous study performed on women who took pills with 20 mcg of EE,12 possibly due to the higher stability of the endometrium when synthetic estrogens were used 15.…”
Section: Discussionsupporting
confidence: 79%
“…In a European Phase III trial, with 20 cycles of observation, only 2.5% of women discontinued treatment prematurely due to bleeding irregularities 13. Our data are higher than the above, but quite similar to those of a large clinical study performed in a real-life setting (27.7%) 14. The discontinuation rate for irregular bleedings that we observed with E2-COCs was higher than that (5.3%) observed in a previous study performed on women who took pills with 20 mcg of EE,12 possibly due to the higher stability of the endometrium when synthetic estrogens were used 15.…”
Section: Discussionsupporting
confidence: 79%
“…Hormonal contraceptive methods and IUDs may induce changes in menstrual bleeding patterns [14][15][16], which can impact willingness to try or continue using these methods, or method satisfaction [6,[17][18][19][20][21][22][23]. Contraceptive-induced menstrual bleeding changes (CIMBCs) may include bleeding patterns which are predictable but diverge from a "typical" menstrual pattern (such as amenorrhea, commonly induced by methods such as progestin-only injectables, or heavy, prolonged bleeding often experienced by copper IUD users [24,25]), or may cause unpredictable bleeding patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a systematic review reported that satisfaction was high for COCs with an extended or continuous regimen, although there was also evidence indicating some users discontinued treatment due to irregular bleeding 30. A prospective longitudinal observational study reported that a pill containing estradiol valerate and dienogest was associated with better outcomes (eg, shorter period, less bleeding, and less menstrual pain) and higher user satisfaction than a progestogen-only pill, with discontinuation rates of 20% and 26%, respectively 33. A systematic review of research on levonorgestrel-releasing IUS found that over three-quarters of users reported symptom improvement and were satisfied with treatment 23.…”
Section: Discussionmentioning
confidence: 99%
“… 30 A prospective longitudinal observational study reported that a pill containing estradiol valerate and dienogest was associated with better outcomes (eg, shorter period, less bleeding, and less menstrual pain) and higher user satisfaction than a progestogen-only pill, with discontinuation rates of 20% and 26%, respectively. 33 A systematic review of research on levonorgestrel-releasing IUS found that over three-quarters of users reported symptom improvement and were satisfied with treatment. 23 Of direct relevance to satisfaction, the current study is one of the first to provide results on the treatment preferences of women with dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%